Menilai Lingkungan Internal Perusahaan : Analisis Strategi melalui Pendekatan Rantai Nilai, Resource-Based View, dan Evaluasi Kinerja - Sifa Khoridatun Nisa; Muna Mumtazah Syahidah; Hesti Kusumaningrum (Jurnal Manajemen Bisnis Era Digital, 2025)
This study aims to evaluate the internal environment of a company through three main approaches: value chain analysis, the resource-based view (RBV), and performance evaluation. Value chain analysis is used to understand activities that contribute to customer value creation. RBV emphasizes the importance of internal resources in achieving sustainable competitive advantage. Performance evaluation assesses the effectiveness of the company's strategy in both financial and non-financial aspects. The study shows that integrating these three approaches can help companies formulate adaptive and highly competitive strategies.